(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2023)
The article is devoted to the peculiarities of the development of physical culture and mass sports. The principle of all aspects of physical education has been developed. The fact that in the process of physical education great opportunities open up forsolving mental, moral and aesthetic problems, and the solution of these problems expands the role of physical education as a factor in the comprehensive development of a personality, is reflected in examples of direct physical education.